EVALUASI KEBIJAKAN PENGELOLAAN PERSAMPAHAN DI KOTA MANADO - JUHRA, ANDIRMAN; LENGKONG, FLORENCE DAICY; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: The purpose of this research is to know and describe the Evaluation of Waste Management Policybased on evaluation criteria such as Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, andaccuracy as for the object of research in Manado City environmental office. The type of research is qualitativeresearch with data collection techniques consist of observation, interview and primary data. While analyticaltechniques by the way, data reduction, data presentation, conclusion. The results of the study indicate thatwaste management policies have been implemented but have not been good because there are still problemsin evaluation criteria such as effectiveness, adequacy, responsiveness, and accuracy. As for the criteria ofefficiency and equity is good. The effectiveness is not good because the vehicle in transporting waste inManado City is still minimal and commonly suffered damage, Efficient for this criterion is good because thecost of retribution paid by the society is in accordance with the services provided, Adequacy in this criterionis still a problem because there are still many people who dumping waste is not in time, Equity for this criterionis good because the cost of retribution has been applied thoroughly in Manado City, Responsiveness of thiscriterion also not yet run properly in case because society still apathy or less care of cleanliness ofenvironment, in criterion Accuracy still not good also because there are still many districts do not have wastemanagement programs such as Bank garbage program, TPSS, and TPS 3R.Keywords: policy, evaluation, effectiveness, efficiency, adequacy, equity, Responsiveness, and accuracy